Modified breathing relaxation in OSCE participants: A randomized controlled trial - Tia Nurhilmiah; Azhar Alamsyah; Asep Suryadin (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Academic examinations, especially practical exams such as OSCE, often trigger high levels of anxiety among nursing students. Anxiety arises from environmental pressure, limited time, and strict regulations, which negatively affect students’ performance. Non-pharmacological interventions, particularly breathing relaxation techniques combined with spiritual elements, are considered effective to reduce anxiety before examinations. Purpose: To identify the effect of modified deep breathing relaxation techniques with dzikr on the anxiety levels of nursing students facing OSCE at Muhammadiyah University of Sukabumi. Method: This research was a randomized control trial with parallel group design. A total of 36 nursing students were recruited and divided equally into intervention and control groups using simple random sampling. The intervention group received modified deep breathing relaxation combined with dzikr prior to OSCE, while the control group did not receive the intervention. Anxiety was measured using the Zung Self Anxiety Scale (ZSAS) before and after the OSCE. Data were analyzed using Shapiro-Wilk, Levene test, paired t-test, independent t-test, and Cohen’s d. Results: The findings showed a significant reduction in anxiety in the intervention group, with the mean score decreasing from 66.72 to 53.72 (p = 0.000). Conversely, the control group experienced an increase in anxiety, from 43.17 to 48.39 (p = 0.017). The difference between groups was statistically significant (p = 0.049) with a medium effect size (0.682). Conclusion: Modified deep breathing relaxation combined with dzikr is effective in reducing anxiety among OSCE participants. Nursing education institutions are encouraged to apply this technique as part of routine preparation to help students manage anxiety before practical examinations.